Multiple Solutions for Elliptic px,qx-Kirchhoff-Type Potential Systems in Unbounded Domains - Nabil Chems Eddine; Abderrahmane El Hachimi (International Journal of Differential Equations)
In this paper, we establish the existence of at least three weak solutions for a parametric double eigenvalue quasi-linear elliptic px,qx-Kirchhoff-type potential system. Our approach is based on a variational method, and a three critical point theorem is obtained by Bonano and Marano.